The porphyry copper system and the precious metal-gold potential - Gendall, Ian Richard (Rhodes University, Faculty of Science, Department of Geology, 1994)
It has been established that porphyry copper/copper-gold deposits have formed from I Ma to 2 Ga ago. Generally, they are related to the Mesozoic-Cenozoic interval with few reported occurrences from the Palaeozoic or Precambrian. A reason cited is the erosion of these deposits which are often related to convergent plate margins and orogenic belts. Observations of the alteration and mineralisation within and around porphyry copper/copper-gold systems have been included in numerous idealised models. These alteration and mineralisation patterns are dependent on the phases of intrusion, the tectonic setting and rock type, depth of emplacement and relationship to coeval volcanics, physiochemical conditions operative within and surrounding the intrusive and many other mechanical and geochemical conditions. Island arc and cratonic arc/margin deposits are generally considered to be richer in gold than their molybdenum-rich, intra-cratonic counterparts. Metal zonation may occur around these copper/copper-gold deposits, e.g. copper in the core moving out to silver, lead, zinc and gold. This zonation is not always present and gold may occur in the core, intermediate or distal zones. Examples of gold-rich porphyry deposits from British Columbia, Chile and the SW Pacific Island regions suggest gold is closely associated with the potassic-rich zones. Generally these gold-rich zones have greater than 2% magnetite and a high oxygen fugacity is considered to be an important control for gold deposition. High Cl contents within the magma are necessary for gold mobility within the host intrusive centres. Beyond this zone HSâ‚‚ becomes an important transporting ligand. Exploration for porphyry copper-gold deposits includes an integrated geological, geophysical and geochemical approach. Petrographic work through to Landsat imagery may be used to determine the chemical conditions of the system, ore association, favourable structural zones and alteration patterns, in order to focus exploration activities.
Keywords: Copper ores; Porphyry; Gold ores -- Geology; Prospecting